2007
DOI: 10.1093/annonc/mdm376
|View full text |Cite
|
Sign up to set email alerts
|

Results of a prospective dose-intensive regimen in 27 patients with small cell carcinoma of the ovary of the hypercalcemic type

Abstract: Background:The evaluation of first-line intensive combination therapy in small cell carcinoma of the ovary (SCCO). Patients and methods: Debulking surgery; four to six cycles of chemotherapy with cisplatin (P) 80 mg/m 2 day 1, adriamycin (A) 40 mg/m 2 day 1, vepeside (V) 75 mg/m 2 /day days 1-3, cyclophosphamide (EP) 300 mg/m 2 /day days 1-3, every 3 weeks and granulocyte colony-stimulating factor with, in case of a complete remission, high-dose chemotherapy with carboplatin, vepeside, cyclophosphamide and ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
55
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(56 citation statements)
references
References 18 publications
1
55
0
Order By: Relevance
“…The second developed isolated brain metastases but remains in remission after cranial irradiation and further chemotherapy. Pautier et al have shown the 3-year survival to improve to 49% in their series of 27 patients with dose-intense chemotherapy [26]. The important aspect of our patients' treatment may be the weekly dose-dense and dose-intense scheduling rather than the individual drugs.…”
Section: Discussionmentioning
confidence: 98%
“…The second developed isolated brain metastases but remains in remission after cranial irradiation and further chemotherapy. Pautier et al have shown the 3-year survival to improve to 49% in their series of 27 patients with dose-intense chemotherapy [26]. The important aspect of our patients' treatment may be the weekly dose-dense and dose-intense scheduling rather than the individual drugs.…”
Section: Discussionmentioning
confidence: 98%
“…Nevertheless, the prognosis generally remains dramatically poor. Few large studies have been conducted [1,[5][6][7], the more significant one by Young [4]. Adjuvant regimens were derived from epithelial carcinoma therapies, consisting of cisplatinum, cyclophosphamide with or without doxorubicine and hexamethylmelamine; in all cases only short-term favourable responses have been obtained [5].…”
Section: Discussionmentioning
confidence: 99%
“…Another limited number of long-term survivors with advanced stages disease at diagnosis had received regimens consisting of 5 to 6 antineoplastic agents (combination of vinblastine, cisplatin, cyclophosphamide, bleomycin, adriamycin, etoposide) [8,9]. Other series, the most recent of which by Pautier in 2007, describe poli-chemotherapy as first line treatment in SCCO of the hypercalcemic type followed by high dose consolidation chemotherapy leading to an exceptionally better outcome [6,7]. In our experience, this therapeutic attempt was unsuccessful.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Optimal management of patients is not well defined; in literature several and different treatment strategies and chemotherapy are reported but in few cases due to the rareness of the disease, Harrison et al presented a review of the management of 17 cases in a Gynecological Cancer Intergroup (GCIG) study, with poor results showed [7]. In this context there are no evidence based recommendations nor guide lines (Table 2) [1,3,[8][9][10][11][12][13][14]. We present and discuss a case of SCCOHT in a young patient, as well a review of the literature about ovarian small cell tumors treatment.…”
Section: Introductionmentioning
confidence: 99%